1979
DOI: 10.1080/00222895.1979.10735193
|View full text |Cite
|
Sign up to set email alerts
|

Motor Schema Formation and Retention in Young Children

Abstract: The variability-of-practice hypothesis, a major prediction of Schmidt's (1975) motor schema theory, was tested in an attempt to investigate motor-schema formation. In addition, schema retention was observed after a 2-week retention interval. The task involved preschool children in tossing a bean bag for appropriate distance. Four treatment groups received 100 practice trials equally divided over five days. Variation was provided by varying the weights of the bean bags. The testing situations involved tossing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 6 publications
2
12
0
2
Order By: Relevance
“…This finding suggests another factor that may affect sensitivity to changing contingencies: the range of behavior that has been instructed. This is consistent with Weiner's (1969Weiner's ( , 1970a findings, and with the literature on transfer of learning that indicates that test performance on a novel task is facilitated by training on a variety of tasks (Callantine & Warren, 1955;Carson & Wiegand, 1979;Crafts, 1927;Dashiell, 1924;Duncan, 1958;Ellis, 1965;Ellis, Parente, Grah, & Spiering, 1975;Johnson & Stratton, 1966;Kelso & Norman, 1978;McCracken & Stelmach, 1977;Naylor, 1977;Newell & Shapiro, 1976). Perhaps instruction on a variety of schedules produces responding that changes when the contingencies change.…”
supporting
confidence: 85%
“…This finding suggests another factor that may affect sensitivity to changing contingencies: the range of behavior that has been instructed. This is consistent with Weiner's (1969Weiner's ( , 1970a findings, and with the literature on transfer of learning that indicates that test performance on a novel task is facilitated by training on a variety of tasks (Callantine & Warren, 1955;Carson & Wiegand, 1979;Crafts, 1927;Dashiell, 1924;Duncan, 1958;Ellis, 1965;Ellis, Parente, Grah, & Spiering, 1975;Johnson & Stratton, 1966;Kelso & Norman, 1978;McCracken & Stelmach, 1977;Naylor, 1977;Newell & Shapiro, 1976). Perhaps instruction on a variety of schedules produces responding that changes when the contingencies change.…”
supporting
confidence: 85%
“…For motor tasks, the data suggest that subsequent test performance is greater after mixed practice (see Bjork, 1994, for a review). In Carson and Wiegand (1979), for instance, young children learned to throw bean bags of different weights at a target, and their subsequent test performance was greater when the practice throws for each particular weight were intermixed and not blocked by weight.…”
Section: Blocked Versus Mixed Practicementioning
confidence: 98%
“…Most of the previous studies of interleaving examined its effects on motor skills (e.g. Carson & Wiegand, 1979; Hall, Domingues, & Cavazos, 1994; Keller, Li, Weiss, & Relyea, 2006; Landin, Hebert, & Fairweather, 1993; Shea & Morgan, 1979). For instance, in the study reported by Hall et al, college baseball players practiced hitting three types of pitches (e.g.…”
Section: Literaturementioning
confidence: 99%